Paediatrics for students and practitioners - Chaurasia, D.D (CBS Publishers & Distributors Pvt.Ltd., 2000)
The present book is aimed to provide simple systemetized and complete book on Pediatrics for undergraduate students as well as practitioners. The difficulties of students at various steps made me feel to write a complete book which covers all aspects in up-to-date and concise manner. At the beginning of this book chapter on clinical methods in Pediatrics has been devoted as child differs in many respects from those employed in the case of adult. The text is intended to be comprehensive well described in a simple language. Chapter on growth and development is presented in easy and assimilable form. Diseases of infancy and childhood are described with clinical etiological pathological and radiological basis of diagnosis and management with exclusive pediatric approach. The text is illustrated with photographs diagrams and skiagrams which help in grasping the subject in easy way. The chapter on practical procedures in pediatrics will provide guide to deal with patient at dispensary clinic hospital or at home. Drug dosage in children is presented in convinient form along with trade names and preparations available in the market. It will help clinician to write correct prescription for the patient.